The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00431-018-3177-z
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a board game approach to children’s involvement in family-based weight management vs. traditional family-based behavioral counseling in primary care

Abstract: Family-based behavioral group treatment and game (Kaledo) intervention were found to be effective in childhood obesity management in this research. There was no significant difference between the two interventions. According to this study, these intervention models can be advised to primary care physicians to be used in the management of childhood obesity. What is Known: - Family-based behavioral group treatment is known as the most efficient model for childhood obesity management. What is New: - In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 15 publications
3
26
0
7
Order By: Relevance
“…In nutrition, similar increases in knowledge was found by E. Viggiano et al (2018) in their attempt to improve nutrition knowledge and change eating behavior through board gameplay. The authors randomly placed Italian elementary students in two groups, where the experimental group played a board game for 20 weeks, while the control group did not play the game.…”
Section: Facilitate Learning Of Various Topics and Skillssupporting
confidence: 62%
See 3 more Smart Citations
“…In nutrition, similar increases in knowledge was found by E. Viggiano et al (2018) in their attempt to improve nutrition knowledge and change eating behavior through board gameplay. The authors randomly placed Italian elementary students in two groups, where the experimental group played a board game for 20 weeks, while the control group did not play the game.…”
Section: Facilitate Learning Of Various Topics and Skillssupporting
confidence: 62%
“…The current review reveals the relationship between board games and learning, and highlights the heterogeneity of board game research in terms of field of study, countries, or research settings. Researchers in different fields and settings have explored learning and board games, and showed that board games are instrumental for learning various subjects such as mathematics (Elofsson et al, 2016;Hendrix et al, 2018), health (Olympio & Alvin, 2018;E. Viggiano et al, 2018), and medicine (Cutumisu et al, 2019;Lavender et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of tools were used in primary care settings (Ball et al, 2013;Cloutier et al, 2013;Oettinger et al, 2009;Polacsek et al, 2009;Rutkowski & Connelly, 2016 Woolford et al, 2009). All tools were described for use by paediatricians (Ball et al, 2013;Cloutier et al, 2013;Oettinger et al, 2009;Polacsek et al, 2009;Pollak et al, 2016;Provvidenza et al, 2017;Rutkowski & Connelly, 2016;Salahuddin et al, 2018;Sen et al, 2018;Townsend et al, 2018;Vaczy et al, 2011;Wislo et al, 2013;Woolford et al, 2009), with two also aimed at nurse practitioners (Rutkowski & Connelly, 2016;Vaczy et al, 2011), three at nurses (Ball et al, 2013;Provvidenza et al, 2017;Rutkowski & Connelly, 2016) and one for physician assistants (Salahuddin et al, 2018). Four articles described tool use with other HCPs, including nutritionists, dieticians and exercise specialists (Ball et al, 2013;Polacsek et al, 2009;Provvidenza et al, 2017;Vaczy et al, 2011).…”
Section: Targeted Users and Audiencesmentioning
confidence: 99%